The adsorption mechanisms of algae-bacteria symbiotic system and its fast formation process. (November 2020) - Li, Lixin; Liu, Wanmeng; Liang, Taojie; Ma, Fang
Graphical abstract: Highlights: The formation of the ABSS was described by SEM and zeta potential. Zeta potential and SBET play a key role in the early stage of adsorption. The role of EPS accounted for 84.22% for adsorption capacity. The formation process of ABSS could be divided into the fast stage and slow stage. Abstract: The formation process of the algae-bacteria symbiotic system (ABSS) was analyzed, and the formation adsorption conditions were optimized. The role of extracellular polymeric substances (EPS), specific surface area and zeta potential in adsorption mechanisms were assessed and proposed. The results showed the dry weight of the ABSS and adsorption efficiency of microalgae reached the highest under the conditions of 25 °C, pH 6.0, 160 rpm and CaCl2  2.0 mg/mL. The process of the ABSS formation could be mainly divided into the fast stage and slow stage. The roles of EPS, specific surface area and zeta potential accounted for 84.22%, 5.17% and 10.61% of the adsorption capacity, respectively. EPS dominated the formation of the ABSS. The results indicated that mycelial pellets were biosorption materials and had the characteristics of chemical materials.